Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1959
DOI: 10.1084/jem.109.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Turnover and Tissue Exchange

Abstract: Chemical nitrogen balance studies leave much to be desired in supplying information about internal protein metabolism, relying, as they do, on net differences between intake and output. By isotopically labeling plasma and tissue proteins valuable information concerning the turnover, transport, and equilibria of these proteins under normal basic conditions has been obtained. The present studies deal with some of these aspects of internal metabolism under conditions of altered nitrogen balance.The protein metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
2
4
0
Order By: Relevance
“…The latter may be related to the higher levels of circulating lipopolysaccharide observed in the metabolic syndrome (123) , also linked to the maintenance of low-key inflammation (124,125) caused by increased intestinal bacteria activity (126) . These findings hint to the postulated excess 2-amino-N, in agreement with the higher availability of amino acids and energy to increase protein turnover (127,128) and to maintain a fully functional immune system (129) observed in the metabolic syndrome.…”
Section: Health Consequences Of Hampered Nitrogen Excretion In the Obesesupporting
confidence: 65%
“…The latter may be related to the higher levels of circulating lipopolysaccharide observed in the metabolic syndrome (123) , also linked to the maintenance of low-key inflammation (124,125) caused by increased intestinal bacteria activity (126) . These findings hint to the postulated excess 2-amino-N, in agreement with the higher availability of amino acids and energy to increase protein turnover (127,128) and to maintain a fully functional immune system (129) observed in the metabolic syndrome.…”
Section: Health Consequences Of Hampered Nitrogen Excretion In the Obesesupporting
confidence: 65%
“…This was in line with previous results obtained in rats and dogs (14,42) and was also consistent with data in humans showing the lack of effect of diets supplying 9% or 24% of energy as protein, but containing identical levels of energy and fat, on albumin, fibrinogen, or fibronectin synthesis rates (6). These results also agree with the weak association demonstrated between albumin FSR and the level of dietary protein, when these ranged from the recommended daily allowance to an excess value of 25% (39).…”
Section: Discussionsupporting
confidence: 94%
“…The concentration of albumin in the glomerular filtrate of a number of animal species has been estimated to be in the order of 20 mg/100 ml (1-4), a small fraction being Received for publication 26 October 1970 and in revised form 18 January 1971. excreted while the remainder is absorbed by the renal tubule epithelial cells. If this were true of the rat, for instance, the animal would filter and absorb an amount of albumin equivalent to its total albumin pool each day (5). Renal micropuncture studies in rats and dogs have revealed albumin concentrations in proximal tubule fluid in the order of 2-10 mg/100 ml or more (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%